MODELING OF THE EFFECTIVENESS OF WETLAND VEGETATION AS EXTREME WAVE REMOVAL IN MANGROVE ECO-TOURISM AREA PAGATAN BESAR VILLAGE - IRA PUSPITA DEWI; NURSALAM (CV KULTURA DIGITAL MEDIA, 2021)
This study examines the effectiveness of mangroves in long distances to the beach in the Mangrove ecotourism area of ​​Pagatan Besar Village. This study aims to determine the effectiveness of mangroves against extreme waves based on wave transformation before and after passing through mangrove vegetation. Data collection methods used are field research, literature and secondary data. The study was conducted by modeling the CMS Wave – SMS structure which predicts changes in height and deflection of extreme waves during the highest tide (Highest Astronomic Tide / HAT) that interacts with mangrove vegetation as a natural beach. The results obtained show that at stations overgrown with mangroves, the waves tend to be still high when approaching the mainland. This is different from Stations 2 and 3 which are overgrown with mangroves. The waves tend to decrease before approaching land. In Profile 1 (not overgrown with mangroves) and Profile 3 (covered with thin mangroves) the wave height is 75 meters from the shoreline (in front of the mangroves) the wave height is 0.31 m and at the back of the mangrove is still 0.01 m on the beach and the back of the mangroves. As for profile 2 (wide mangrove beach) at a distance of 150 m from the shoreline, the wave height has decreased to 0.26 m at the back of the mangrove. The wave height continues to decrease to 0.00 m or has run out.